Tinjauan Yuridis Persyaratan Akreditasi dalam Pengadaan Pegawai Negeri Sipil - Risang Pujiyanto; Netti Iriyanti; Sonny Taufan (Fakultas Hukum Universitas Islam Indonesia, 2018)
Accreditation requirements in Procurement of Civil Servants in 2017 raise a controversy because according to the Ombudsman of the Republic of Indonesia these conditions are discriminatory. This study examines the suitability of accreditation requirements in the Procurement of Civil Servants in 2017 with the applicable laws and regulations. This research is a normative study using the legal approach. The results show that the conditions for accreditation are merely additional requirements and needed to guarantee the legality of the education attainment of an applicant. Accreditation requirements for different general formation paths in each department have yet to be in accordance with the principle of equality as mentioned in one of the Good Governance General Principles.